2021
DOI: 10.3390/jpm11080802
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Glucose Metabolism Disorders, Assessment the Disse Insulin Resistance Index and Hospital Prognosis of Coronary Artery Bypass Surgery

Abstract: Objective: To study insulin resistance markers and their relationship with preoperative status and hospital complications of coronary artery bypass grafting (CABG) in patients with type 2 diabetes, prediabetes and normoglycemia. Methods: We included 383 consecutive patients who underwent CABG. Patients were divided into two groups—with carbohydrate metabolism disorders (CMD, n = 192) and without CMD (n = 191). Free fatty acids and fasting insulin in plasma were determined, and the Disse, QUICKI and revised QUI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(49 reference statements)
0
2
1
Order By: Relevance
“…This is consistent with the conflicting data of our studies. In a study in 2021, we showed that the Disse IR index was an independent factor in the development of postoperative complications [15]. At the same time, in the present study, one of the IR indices-the Revised-QUICKI-turned out to be higher in the group with a combined endpoint (complications + duration of hospitalization), but did not have an independent influence on the development of this combined endpoint.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This is consistent with the conflicting data of our studies. In a study in 2021, we showed that the Disse IR index was an independent factor in the development of postoperative complications [15]. At the same time, in the present study, one of the IR indices-the Revised-QUICKI-turned out to be higher in the group with a combined endpoint (complications + duration of hospitalization), but did not have an independent influence on the development of this combined endpoint.…”
Section: Discussioncontrasting
confidence: 53%
“…Diagnosis of carbohydrate metabolism disorders was carried out in accordance with the current recommendations [18] and was described in detail by us previously [15]. Determination of free fatty acids in blood serum was carried out using the spectrophotometric method, using standard test systems from "Thermo Fisher Scientific" (Helsinki, Finland) on a Konelab 30i automatic biochemical analyzer from the same company.…”
Section: Assessment Of Glycemic Status and Insulin Resistance Indicesmentioning
confidence: 99%
See 1 more Smart Citation